INVESTIGATION OF THE NEUTROPHIL-TO-LYMPHOCYTE RATIO IN ELDERLY PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT THONG NHAT HOSPITAL - Thị Kim Cương, Lê; Thị Ngọc Hạnh, Hồ; Thị Hoài, Cao; Đình Dần, Đặng; Thế Hoàng, Ngô; Thanh Vy, Nguyễn; Thị Kim Tiến, Nguyễn; Thị Vân, Cao (Journal of Health and Aging, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of mortality and disability worldwide. Among elderly patients, COPD not only reduces quality of life but also places a significant burden on healthcare systems. Chronic inflammation plays a key role in the pathogenesis of COPD. In recent years, peripheral blood inflammatory markers such as the neutrophil-to-lymphocyte ratio (NLR) have gained attention as useful tools for assessing inflammation and predicting disease prognosis. However, in Vietnam, especially among elderly patients- research on the role of NLR in monitoring and managing COPD remains limited. Therefore, we conducted the study titled: “Investigation of Neutrophil-to-Lymphocyte Ratio in Elderly Patients with Chronic Obstructive Pulmonary Disease at Thong Nhat Hospital”. To determine the NLR levels in elderly patients with COPD and evaluate the relationship between NLR and disease severity. Additionally, to compare NLR values across different patient subgroups based on factors such as age, gender, BMI, medication usage, comorbidities, and to investigate the correlation between NLR and the inflammatory marker CRP. Sectional descriptive study conducted on elderly COPD patients visiting the respiratory outpatient clinic at Thong Nhat Hospital. From January 2025 to May 2025, we collected data from 221 elderly COPD patients. The mean age was 71 (65-77) years, Males accounted for a higher proportion than females. The mean NLR was 3,3 (2,2 – 6,2), CRP (mg/L) 4,3 (2,6 - 9,5), NLR showed a weak but statistically significant negative correlation with FEV1 (r = -0.147, p < 0,029) and a statistically significant positive correlation with CRP (r = 0,5012, p < 0,0001). Our study demonstrates that NLR is weakly but significantly inversely correlated with pulmonary function (FEV1), and positively correlated with CRP levels, indicating its potential role in assessing disease severity and inflammatory status.